TORCH - A Cherenkov based time-of-flight detector - Van Dijk, M; Brook, N; Castillo García, L; Cowie, E; Cussans, D; D'Ambrosio, C; Fopma, J; Forty, R; Frei, C; Gao, R; Gys, T; Harnew, N; et al. (Elsevier, 2014)
TORCH is an innovative high-precision time-of-flight system to provide particle identification in the difficult intermediate momentum region up to 10 GeV/c. It is also suitable for large-area applications. The detector provides a time-of-flight measurement from the imaging of Cherenkov photons emitted in a 1 cm thick quartz radiator. The photons propagate by total internal reflection to the edge of the quartz plate and are then focused onto an array of photon detectors at the periphery. A time-of-flight resolution of about 10-15 ps per incident charged particle needs to be achieved to allow a three sigma kaon-pion separation up to 10 GeV/c momentum for the TORCH located 9.5 m from the interaction point. Given ~30 detected photons per incident charged particle, this requires measuring the time-of-arrival of individual photons to about 70 ps. This paper will describe the design of a TORCH prototype involving a number of ground-breaking and challenging techniques.